The post-bureaucratic parasite: Contrasting narratives of organizational change in local government - Carl Rhodes (Management Learning, 2011)
This article investigates the relationship between learning, bureaucracy and post-bureaucracy as manifest in a local government council in the Australian state of New South Wales. Empirically, we compare the culturally dominant narrative of the necessity and desirability of post-bureaucracy in public management, the managerial narrative of this particular organization and its restructure, and the local accounts of learning from employees who were immersed in the changing work environment. Our analysis confirms that post-bureaucracy is not an ideal form that exceeds or surpasses bureaucracy, but acts as another marker for the bureaucracy’s ability to survive and adapt. The article’s contribution lies in its exploration of the character of this adaptation. We contend that post-bureaucracy acts a parasite that both relies on and disturbs the practice of bureaucracy while failing to substantively challenge it. Moreover, like a parasite post-bureaucracy requires the ongoing vitality of its host in order to continue to nourish itself.